Oshkosh Scholar - Cowling, Audrey; Schuhart, Hope; Gearhart, Amy; Daron, Derek; Kuchera, Anthony; Hathaway, Chris; Mischler, Steven; Stroik, Jared; Ruff, Chelsea; Sanchez Vinueza, Dayana J. (My University, 2010)
You might not know that the tagline for Oshkosh Scholar is "A journal of undergraduate discoveries." The editorial team is lucky to share in these discoveries each year, and we're excited to bring them to you today. Allow me to give you, our readers, a little peek inside this year's amazing volume. All research begins on a path that has been trod by scholars who came before. Sometimes, however, the path is altered by new findings. Several articles in this volume tackle what we think we know and give us new ways of viewing the world. Chris Hathaway and Anthony Kuchera take us on a journey to the constellation Monoceros, the busy birthplace of new stars, to update our knowledge of how stars form. Dayana Sanchez Vinueza challenges what we know about globalization, and finds that increased international trade does very little to reduce poverty. Steven Mischler pits classic philosophers against modern-day philosophers, illustrating that conceptions of love endure and are coherent across time. Audrey Cowling sorts out the results of animal-assisted therapy on individuals with dementia and provides insight into the circumstances under which animal therapy can be most beneficial to this population. Chelsea Ruff and Amy Gearhart provide insight into the feminine experience in literature and politics. Ruff teases out the unique ways in which complex female characters in two Nalo Hopkinson novels attempt to attain wholeness despite harsh physical realities. Gearhart explores the impact of electoral systems and quotas on female representation in national legislatures in Latin America, showing how electoral rules can make all the difference for female candidates. Other pieces critically reexamine prominent historical figures, looking at them through uncommon lenses. Jared Stroik examines whether or not Richard I's bloody "Massacre at Acre" was part of a last-ditch military strategy or the work of a heartless brute. James Madison's presidency is put under Derek Daron's microscope, and Daron questions Madison's legacy as one of our "great" American presidents. Hope Schuhart maintains that presidential human rights records are an important piece of any overall evaluation of leadership and analyzes Harry Truman's record in this regard.
We are delighted to present this fifth edition of Oshkosh Scholar, a collection of undergraduate student research. This publication displays the ingenuity, curiosity, and academic diversity present at UW Oshkosh. It gives students the opportunity to further their research through collaboration with faculty members and allows them to experience the rewarding rigors of publication as they work alongside our team of editors and reviewers to see their work reach its fullest potential. This high-impact instructional practice offers an exciting chance for students to be engaged in their own learning. For students who want to maximize their education, faculty-mentored research gives them the opportunity to cultivate their ideas in a way that extends far beyond the classroom. These partnerships enrich the individual students and, in turn, the University, developing an environment where active learning is not only encouraged, but celebrated. We are proud to showcase some of the finest examples of this undergraduate research
Keywords: College students; Research; University of Wisconsin - Oshkosh; Students; Undergraduate research